Managing water: technology, economics and nature - Roseta-Palma, C. (Encontro Ciência, 2019)
Water is essential to life, so water management strategies have been defined in all human societies. Water technology advanced massively in the 20th century, allowing for huge supply, drainage and flood control systems to be built. However, it has become clear that supply-augmentation per se might not be the best solution for either scarcity or water quality problems. Economists have brought new demand management tools to water systems, with some positive results, but economic instruments are no panacea for water management, especially in a context of climate change with a higher expected frequency of extreme events. In this presentation I highlight the potential of nature-based solutions for water management, emphasizing their role in cost reduction, diversified co-benefits, and contribution to risk reduction. Although technology will always be useful, and economic instruments contribute to improve resource allocation, the challenges ahead are numerous. Nature-based solutions must be brought into water policies.